The Moderating Role of Technology on the Link between Strategic Training and Performance of State Ministries: Perspectives from Kenya - Selline, Indara; Henry, Kegoro; Dina, Otieno (European Journal of Business and Strategic Management, 2023)
Purpose: The purpose of this study was to examine the moderating role of technology on the link between strategic training and performance of State ministries in Kenya. Human capital theory was utilized to inform this study. Methodology: Cross-sectional research design was adopted in the collection and analysis of data. The study's target population was the 13 Kenyan government Ministries. The target population of the study consisted of 344 employees from 13 government ministries in Kenya. 185 respondents made up the study's sample size. To choose respondents, a stratified sample strategy was utilized. Structured questionnaires with both open and closed-ended questions were used to gather primary data. Acts of Parliament, service delivery charters, Vision 2030, session papers on public service delivery, and yearly performance reports were used to gather secondary data. Using experts in human resource management, the validity of the study instrument was assessed. The Cronbach Alpha formula, which adopted reliability coefficients of 0.7 as advised in literature, was used to assess reliability. Using the content analysis method, major themes from both written and spoken word were examined, and deductive arguments were produced based on the fundamental assumptions of the theories. Statistical Package for Social Sciences version 24 was used to perform the descriptive statistics, correlation, and regression analyses on the quantitative data. At a 95% confidence level and a 5% significance level, mean scores, standard deviations, percentages, and frequencies were utilized to define the components of each variable. Tables and graphics were used to present the examined data. Findings: The findings of this study disclosed that strategic training had a significant positive effect on performance of government ministries in Kenya (r=.674, p-value=.000) while technology positively moderated the relationship between strategic training and performance of Kenyan government ministries (r=.672, p-value=.000). The study concluded that, if properly adopted, strategic training combined with technology can effectively explain performance of government ministries in Kenya. Unique Contribution to Theory, Practice and Policy: This study recommends that for effective performance of government ministries in Kenya, embracing strategic training and technology is key. This study adds to theory by disclosing that managers can make decisions anchored on human capital theory as well as inform policies formulated and implemented.